Analysis of the Earth Movement over the Equatorial Region by using the Ionosonde Observation Data - Nagarajoo, K (International Journal of Integrated Engineering, 2009)
This paper focuses on the ionospheric variability observed in the F2 layer during a seismic event at equatorial region. The analysis using critical frequency, fc, shows that there is relationship between the ionospheric variations and the occurrence of earthquake. The fc of the F2 layer (fcF2) and the minimum virtual height (h’F2) data were measured using ground-based ionosonde that has been stationed in Wireless and Radio Science Centre (WARAS), UTHM (1.860 N, 103.080 E). Two statistical techniques, which are the median and mean based techniques, were used to examine the possible relationship between the Earth movement and the variation of the fcF2 in the ionosphere. In this research, five cases of strong earthquakes in Indonesia with Ritcher scale from 6.4 to 9.1 for the year 2004 and 2007 were chosen. However, only two cases are in good agreement with the results obtained from the previous research that was done in India. Both earthquakes occurred at off west coast of Northern Sumatra (M=9.1) and Java (M=7.5). The results showed that fcF2 are reducing 23 to 26 days prior to the earthquake occurred at the off west coast of Northern Sumatra and within 5 days prior to the Java earthquake. Data fitting was done to the ionospheric perturbations (i.e. fc) before and after the earthquake by using the mathematical equations from Matlab. The fittings show better approximation with the mathematical equations in the 5th order. Nevertheless, those equations were not good enough to be an analytical mathematical model to represent the precursor for any earthquake event because the ionosphere varies diurnally.